Hydrothermal Reactions for Materials Science and Engineering 1989
DOI: 10.1007/978-94-009-0743-0_39
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ultrafine Tetragonal ZrO2 Powder Under Hydrothermal Conditions

Abstract: Ultrafine tetragonal ZrO2 powder was prepared by hydrothermal treatment at 100 MPa of amorphous hydrous zirconia with distilled water and LiCl and KBr solutions. The resulting powder consisted of well‐crystallized particles; at 200°C, the particle size was 16 nm and at 500°C, 30 nm. Under hydrothermal conditions tetragonal ZrO2 appears to crystallize topotactically on nuclei in the amorphous hydrous zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Monoclinic ZrO 2 precipitation is a pH-dependent process and it was reported that monoclinic ZrO 2 precipitates from the acidic (pHo1) and alkaline (pH414) solutions [3]. The presence of the hydroxo (-OH) complex, or amorphous zirconia, as the precursor facilitates the formation of tetragonal ZrO 2 phase under hydrothermal conditions [3,14]. Therefore, formation of pure monoclinic ZrO 2 at pHo1 is consistent with the literature.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Monoclinic ZrO 2 precipitation is a pH-dependent process and it was reported that monoclinic ZrO 2 precipitates from the acidic (pHo1) and alkaline (pH414) solutions [3]. The presence of the hydroxo (-OH) complex, or amorphous zirconia, as the precursor facilitates the formation of tetragonal ZrO 2 phase under hydrothermal conditions [3,14]. Therefore, formation of pure monoclinic ZrO 2 at pHo1 is consistent with the literature.…”
Section: Methodssupporting
confidence: 83%
“…3 and 7), tetragonal phase forms in addition to monoclinic phase. This difference results from different starting materials (i.e., solution versus aqueous gel) because in situ crystallization of amorphous aqueous zirconia proceeds via a dissolution-precipitation process rather than a topotactic crystallization (e.g., structural rearrangement of amorphous hydrous zirconia), and nanocrystalline monoclinic (m), tetragonal (t) and cubic (c) ZrO 2 phases form practically simultaneously during hydrothermal treatment of zirconia gel depending on the hydrothermal conditions, particularly pH [6,14,17,18]. Denkewicz et al [18] reported that crystallization takes place by an in situ topotactic process in a neutral or mild acidic medium due to low solubility, which facilitates predominantly t-ZrO 2 formation.…”
Section: Resultsmentioning
confidence: 99%
“…Partly or completely stabilized zirconium dioxide ceramic, used as a solid electrolyte in electronic instruments, sensors and oxygen pumps, should correspond to specific requirements: it should be weakly receptive towards gases, have a mechanical strength and impact strength sufficient for preventing the failure of articles during operation [2][3][4][5][6]. Ceramics with a small grain size may be of interest from the point of view of superplastic deformation: during hot forging there is an increase in both the deformation rate and the overall extension with a simultaneous decrease in the size of defects [3][4][5][6][7][8][9][10]. Sintering of stabilized zirconium dioxide nano-ceramic at relatively low temperatures is only possible with observation of the original condition of macrostructure homogeneity for a compact (green body), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Agglomeration is explained by adhesion of particles under the action of Van der Waals forces that increase in the case of nano-particles [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Agglomerates are assumed to be soft if the particles are combined (joined) only by weak attraction forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation